Prospects and Perspectives of Health Impact Assessment: A Systematic Review of the Peer-Reviewed Literature From June 2007 to January 2023 - Nina Lamprecht; Nina Lamprecht; Nina Lamprecht; Tobias E. Erlanger; Tobias E. Erlanger; Jürg Utzinger; Jürg Utzinger; Mirko S. Winkler; Mirko S. Winkler (Frontiers Media S.A., 2024)
ObjectivesIn 2008, an analysis investigating health impact assessment (HIA) practice found that only 6% of HIA-related peer-reviewed publications had a focus on low- and medium-developed countries, whereas 94% were conducted in countries with a high or very high development state. We aimed to update and deepen these observations.MethodsWe conducted a systematic review, searching PubMed and Web of Science for HIA-related papers published in the scientific literature from June 2007 to January 2023. Only applied HIA and papers with HIA as a subject were included.ResultsThe search yielded 3,036 publications and the final selection consisted of 1,019 publications. The annual number of total publications increased considerably over the past 15 years. Whereas research-driven HIA (n = 460) showed a steep increase, step-by-step HIA (n = 71) did not show a clear trend.ConclusionThe gap between the number of HIA-related peer-reviewed publications focusing on low/medium and high/very high developed countries has diminished from 6/94 to 11/89. There is a growing tendency to apply the terminology HIA for health impact modelling studies and quantitative health risk assessments.